RACIAL ANALYSIS OF CARPMINNOW SALMOSTOMA CLUPEOIDES (BLOCH) - Piska, Ravishankar (Indian Journal of Fisheries, 2011)
The present study deals with reciation of the population of two stocks of Salmostoma clupeoides (Bloch) of Qsmansagar and Himayathsagar. The differences between morphometric, meristic and length - weight characters in two water bodies indicated that they are drawn from a common stock and no remarkable differentiation has occurred for placing them under separate natural populations. The differentiation tendencies have commenced but they are not sufficient enough to classify them into separate populations, since they are liable to dissappear with the change of habitat